A New Flavonoid from Malaysian Dipterocarpus cornutus - Wan Zuraida Wan Mohd Zain; Liliwirianis Nawi; Norizan Ahmat; Che Puteh Osman; Yaya Rukayadi (Indonesian Journal of Chemistry, 2021)
Dipterocarpus cornutus Dyer is commonly known as ‘keruing’. It belongs to the family of Dipterocarpaceae, an important timber family in South East Asia. D. cornutus is listed as critically endangered on IUCN Red List. Since no comprehensive study has been documented on the chemical constituents of D. cornutus, there is an urgent need to study this plant comprehensively. Phytochemical study of the stem bark of D. cornutus afforded a new flavonoid (1) and nine known compounds, which consist of flavonoids (2, 3), oligostilbenoids (4, 5, 7, 8, 9, 10), and coumarin (6). The finding of the study contributes to the chemotaxonomic differentiation in the plants of the tribe Dipterocarpae.